Laporan Kasus: Glossitis pada Penderita Anemia Defisiensi Besi - Agus Surachman; Derrida Magista Pariputra; Aris Aji Kurniawan; Maulina Triani; Anindita Laksitasari; Aditya Priagung Prakosa (Fakultas Kedokteran Gigi Universitas Jember, 2022)
Anemia is a common hematological disorder. Anemia is a disorder in which erythrocytes or circulating hemoglobin cannot fulfill their function properly. A 21-year-old woman came to the General Sudirman University Dental and Oral Hospital with complaints of dizziness, weakness, pale face, burning tongue in the oral cavity, stinging sensation on the dorsum of the tongue, and getting sicker when eating spicy food. spicy or hot. Symptoms have been coming and going since last year. Complete blood count was performed and the patient was diagnosed with glossitis due to iron deficiency anemia. Discussion: Glossitis is an inflammation of the tongue characterized by depapilation of the tongue accompanied by pain or burning in the tongue area. Glossitis is one of the oral manifestations of iron deficiency anemia. Patients with anemia can experience glossitis. The therapy given is instructions to the patient to consume foods rich in iron.